Greenhouse gas emissions accounting for ADB energy project economic Analysis guidance note. ([Manila] Asian Development Bank, 2019)
Reporting of emissions of energy projects outside of economic analysis uses a different point of comparison (a baseline scenario) than does economic analysis (a without project scenario). As economic analysis needs to use a consistent set of scenarios across benefit streams, the note recommends and illustrates the use of a without project scenario for calculating emissions effects in project economic analysis.
Keywords: Greenhouse gases -- Environmental aspects; Air quality management -- Economic aspects; Electronic books